2020
DOI: 10.1051/e3sconf/202021102010
|View full text |Cite
|
Sign up to set email alerts
|

An experimental approach to exploring the feasibility of unmanned aerial vehicle and thermal imaging in terrestrial and arboreal mammals research

Abstract: The visual camouflage of many species living in the dense cover of the tropical rainforest become obstacles to conducting species monitoring. Unmanned aerial vehicles (drones) combined with thermal infrared imaging (TIR) can rapidly scan large areas from above and detect wildlife that has a body temperature that contrasts with its surrounding environment. This research tested the feasibility of DJI Mavic 2 Enterprise Dual with FLIR as aerial survey platforms to detect terrestrial and arboreal mammals in the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…In this study hare and roe deer were observed to react to the drone when flying at altitudes below 40 m, despite the M2EA being equipped with noise reducing propellers. Similarly, Rahman et al [22] and Rahman and Setiawan [40] found that flying at altitudes below 50 m increased the risk of disturbing the animals.…”
Section: Flight Parametersmentioning
confidence: 93%
See 3 more Smart Citations
“…In this study hare and roe deer were observed to react to the drone when flying at altitudes below 40 m, despite the M2EA being equipped with noise reducing propellers. Similarly, Rahman et al [22] and Rahman and Setiawan [40] found that flying at altitudes below 50 m increased the risk of disturbing the animals.…”
Section: Flight Parametersmentioning
confidence: 93%
“…[20,21] and deer (Cervidae spp.) [18,22,23], along with forest dwelling species, e.g. koalas (Phascolarctos cinereus) [24] and macaques (Macaca spp.)…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gambar 2. Bingkai video yang memperlihat-kan satwa yang tertutup kanopi pohon selama pemantauan pada (A) malam dan (B) siang hari (Rahman et al 2020).…”
Section: Hasil Dan Pembahasanunclassified